Does α +-Thalassaemia Protect against Malaria? - Pasvol, Geoffrey (PLoS medicine, 2006)
Pasvol discusses a new study in PLoS Medicine that shows that α +-thalassemia protects against severe but not mild malaria. A new study finds that α +-thalassaemia protects against severe but not mild malaria